2017
DOI: 10.1002/jcsm.12265
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of chemotherapy‐induced cachexia by ACVR2B ligand blocking has different effects on heart and skeletal muscle

Abstract: BackgroundToxicity of chemotherapy on skeletal muscles and the heart may significantly contribute to cancer cachexia, mortality, and decreased quality of life. Doxorubicin (DOX) is an effective cytostatic agent, which unfortunately has toxic effects on many healthy tissues. Blocking of activin receptor type IIB (ACVR2B) ligands is an often used strategy to prevent skeletal muscle loss, but its effects on the heart are relatively unknown.MethodsThe effects of DOX treatment with or without pre‐treatment with sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
59
3

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(68 citation statements)
references
References 67 publications
(126 reference statements)
6
59
3
Order By: Relevance
“…In addition to skeletal muscles, cardiac cachexia and associated pathological changes such as arrhythmias may be linked to survival in cancer cachexia . In our hands, however, the C26 tumour burden resulted in only mild cardiac cachexia and sACVR2B treatment did not affect heart size, similarly as earlier . This differs from the results of Zhou et al who reported significant cardiac atrophy which was fully reversed by sACVR2B.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In addition to skeletal muscles, cardiac cachexia and associated pathological changes such as arrhythmias may be linked to survival in cancer cachexia . In our hands, however, the C26 tumour burden resulted in only mild cardiac cachexia and sACVR2B treatment did not affect heart size, similarly as earlier . This differs from the results of Zhou et al who reported significant cardiac atrophy which was fully reversed by sACVR2B.…”
Section: Discussioncontrasting
confidence: 71%
“…Muscle protein synthesis was analysed using surface sensing of translation method as earlier in our laboratory . Briefly, on Day 11 after C26 cell inoculation, mice were anaesthetized and subsequently injected i.p.…”
Section: Methodsmentioning
confidence: 99%
“…Such pre‐clinical considerations must be a focus of future studies in PDAC, given that activin receptor inhibition prolongs survival dramatically in combination with chemotherapy . Alternatively, a limitation of this approach could be the lesser protection of cardiac muscle vs. skeletal muscle with activin blockade or the requirement for inhibition of autocrine signalling in other yet unknown organs.…”
Section: Discussionmentioning
confidence: 53%
“…105 Ghrelin, which is primarily produced in the fundus of the stomach, has been used in disease-related anorexia and conditions of muscle loss like sarcopenia and cachexia. 117 However, while neutralizing antibodies such as MYO-029, AMG 74, and LY2495655 or soluble receptor decoys such as ACE-11 and ACE-031 has significant beneficial effects on muscle mass and strength, they also exhibit several side effects including urticarial, aseptic meningitis, diarrhoea, confusion, fatigue, and unintentional muscle contractions. 63 The small Skeletal muscle wasting in chronic heart failure molecule ghrelin-analogue anamorelin also increased muscle mass but had no effect on muscle strength.…”
Section: Chronic Heart Failure and Muscle Maintenancementioning
confidence: 99%